The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.4062/biomolther.2020.160
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of COX-2 Impairs Colon Cancer Liver Metastasis through Reduced Stromal Cell Reaction

Abstract: Liver colonization is initiated through the interplay between tumor cells and adhesion molecules present in liver sinusoidal endothelial cells (LSECs). This crosstalk stimulates tumor COX-2 upregulation and PGE 2 secretion. To elucidate the role of the LSEC intercellular adhesion molecule-1 (ICAM-1) in the prometastatic response exerted by tumor and stromal COX-2, we utilized celecoxib (CLX) as a COX-2 inhibitory agent. We analyzed the in vitro proliferative and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…COX-2 has been found in high levels in CRC (125). Studies have confirmed that COX-2 is a promoting factor for liver metastasis of CRC, and it can convert arachidonic acid into prostaglandin E2 (PGE2) (138,139). TAMs are the main source of COX-2 in intestinal tumors; PGE2-bound EP4 promotes the differentiation of immunosuppressive M2 macrophages and reduces the expansion of immunostimulatory M1 macrophages (128).…”
Section: Other Biomoleculesmentioning
confidence: 99%
“…COX-2 has been found in high levels in CRC (125). Studies have confirmed that COX-2 is a promoting factor for liver metastasis of CRC, and it can convert arachidonic acid into prostaglandin E2 (PGE2) (138,139). TAMs are the main source of COX-2 in intestinal tumors; PGE2-bound EP4 promotes the differentiation of immunosuppressive M2 macrophages and reduces the expansion of immunostimulatory M1 macrophages (128).…”
Section: Other Biomoleculesmentioning
confidence: 99%
“…Blocking NRP-1 protein led to impaired tumor growth and vascular remodeling[ 39 ]. Interestingly, NRP-1 expression stimulated the activation of HSCs[ 101 ], liver-resident myofibroblast-like cells that contribute to the malignant growth of liver metastasis[ 23 , 24 , 102 ]. The NRP-1-dependent activation boosted tumor proliferation, cell migration, and invasiveness[ 101 ].…”
Section: Liver Cancermentioning
confidence: 99%
“…Some NRP-1 ligands are involved in liver pathologies. For example, VEGF mediates the angiogenic response of LSECs[ 23 ] and is associated with metastatic growth[ 24 ]. Another NRP-1 ligand, TGF-β, mediates the activation of HSCs during fibrogenesis[ 25 , 26 ], leading to liver fibrosis and extracellular matrix (ECM) remodeling during liver metastasis and the creation of a premetastatic niche[ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mueller et al showed that CAF migration is promoted by the presence of tumour cells, although the factors that mediate this migration remain elusive [ 83 ]. Finally, the Arteta group showed that CT-26 CM promoted LSEC and HSC migration and that soluble ICAM-1 pre-treatment of tumour cells enhanced this effect [ 79 , 80 ]. They later showed that tumoural COX-2 was involved in the pro-migratory effects of soluble ICAM-1 [ 80 ].…”
Section: In Vitro Models Studying the Role Of Hscs In Liver Metastasesmentioning
confidence: 99%
“…Finally, the Arteta group showed that CT-26 CM promoted LSEC and HSC migration and that soluble ICAM-1 pre-treatment of tumour cells enhanced this effect [ 79 , 80 ]. They later showed that tumoural COX-2 was involved in the pro-migratory effects of soluble ICAM-1 [ 80 ].…”
Section: In Vitro Models Studying the Role Of Hscs In Liver Metastasesmentioning
confidence: 99%